The pig is an excellent model to determine amino acid digestibility of human foods and to generate data needed to meet human amino acid requirements - Stein, Hans H. (Frontiers in Nutrition, 2024)
The protein value of any food item is determined by the quantity and ileal digestibility of indispensable amino acids in that food. To determine the ileal digestibility of amino acids, an animal model needs to be used, and the pig is the preferred model because values for ileal digestibility obtained in pigs are representative of values obtained in humans. In addition, pigs are omnivorous animals like humans, they are meal eaters, they consume most diets that humans consume, they are easy to work with, and they can be used for repeated determinations of digestibility in many foods. It is, therefore, possible to use pigs to establish a database with digestibility values for human foods and by correcting digestibility values obtained in pigs for the basal endogenous losses of amino acids, it is possible to calculate true ileal digestibility values that are additive in mixed meals. As a consequence, the protein quality of a meal consisting of several food items can be calculated based on digestibility values obtained in pigs.Future work needs to focus on expanding existing databases for amino acid digestibility in foods to include more food items, which will make it possible to estimate the amino acid value of more mixed meals. It is also necessary that the amino acid values in mixed meals be related to requirements for digestible indispensable amino acids in the individuals consuming the meals.The current contribution describes the basic steps in determining amino acid digestibility in human foods using the pig as a model and also outlines future steps needed to further improve amino acid nutrition in humans.